A rare coincidence: facioscapulohumeral muscular dystrophy and breast cancer - Yazici, O.; Aksoy, S.; Ozdemir, N.; Sendur, M.A.N.; Dogan, M.; Zengin, N. (Experimental Oncology, 2013)
Aim: Facioscapulohumeral muscular dystrophy (FSHD) is an autosomally inherited neuromuscular disorder and may be associated with increased cancer risk. Patient: A 69-year old female admitted to hospital with complaint of left axillary mass who had diagnosis of FSHD in her adulthood period. Results: Bilateral breast cancer diagnosis was made and the patient underwent bilateral mastectomy. Following the operation, adjuvant chemotherapy and radiotherapy performed and hormonal therapy started. Conclusion: The patients with congenital muscular dystrophy might have an increased risk of malignancy. We consider that some genetic alterations in FSHD might have contributed to the development of bilateral breast cancer in our patient. Key Words: muscular dystrophy, breast cancer, PTEN.Aim: Facioscapulohumeral muscular dystrophy (FSHD) is an autosomally inherited neuromuscular disorder and may be associated with increased cancer risk. Patient: A 69-year old female admitted to hospital with complaint of left axillary mass who had diagnosis of FSHD in her adulthood period. Results: Bilateral breast cancer diagnosis was made and the patient underwent bilateral mastectomy. Following the operation, adjuvant chemotherapy and radiotherapy performed and hormonal therapy started. Conclusion: The patients with congenital muscular dystrophy might have an increased risk of malignancy. We consider that some genetic alterations in FSHD might have contributed to the development of bilateral breast cancer in our patient.